2019
DOI: 10.1002/cncr.32377
|View full text |Cite
|
Sign up to set email alerts
|

Type and case volume of health care facility influences survival and surgery selection in cases with early‐stage non–small cell lung cancer

Abstract: Background With the expansion of non–small cell lung cancer (NSCLC) screening methods, the percentage of cases with early‐stage NSCLC is anticipated to increase. Yet it remains unclear how the type and case volume of the health care facility at which treatment occurs may affect surgery selection and overall survival for cases with early‐stage NSCLC. Methods A total of 332,175 cases with the American Joint Committee on Cancer (AJCC) TNM stage I and stage II NSCLC who were reported to the National Cancer Data Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…A larger proportion of patients with Medicaid or no insurance was treated at a community cancer center (9.3% and 6.3%, respectively), compared to patients with Medicare or private insurance (4.2% and 3.2%, respectively). Facility type has been noted to be an independent factor affecting prognosis in other cancers [21][22][23], with community cancer centers usually having poorer overall survival when compared to academic/research programs, comprehensive community cancer programs, or integrated network cancer programs. Furthermore, facility volume is often correlated with facility type.…”
Section: Discussionmentioning
confidence: 99%
“…A larger proportion of patients with Medicaid or no insurance was treated at a community cancer center (9.3% and 6.3%, respectively), compared to patients with Medicare or private insurance (4.2% and 3.2%, respectively). Facility type has been noted to be an independent factor affecting prognosis in other cancers [21][22][23], with community cancer centers usually having poorer overall survival when compared to academic/research programs, comprehensive community cancer programs, or integrated network cancer programs. Furthermore, facility volume is often correlated with facility type.…”
Section: Discussionmentioning
confidence: 99%
“…3 Nearly onethird of lung cancer operations are performed by general surgeons, with a majority done in nonacademic settings. 3,4 This heterogeneity creates an opportunity to improve outcomes through centralization of lung cancer surgery, with volume cutoffs to ensure adequate experience. 5,6 The data show no clear relationship between using volume minimums and improved outcomes, however.…”
Section: Bryan M Burt Mdmentioning
confidence: 99%
“…The STS-GTSD disproportionally selects for patients who receive their care at metropolitan academic centers, which are more likely to be higher-volume centers for lung cancer resection to begin with, and have been associated with better short-and long-term outcomes for lung cancer. 4 For example, that national literature demonstrates that 8% of patients receive lung cancer surgical care at a facility meeting both hospital and surgeon standards, and yet 52% of the study population of Farjah and associates met these standards. 8,12 The overrepresentation of patients from highvolume academic centers within the STS-GTSD ignores well documented income, geographic, racial/ethnic, and insurance disparities in terms of receipt of lung cancer surgery, as well as access to high-volume centers.…”
Section: Integrating Social Determinants In the Sts-gtsd And Volume-outcomes Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…6 Several studies have shown improved outcomes among patients treated at academic facility types versus community health care facilities for multiple cancer sites, including lung cancer. [17][18][19][20] Among patients with early-stage lung cancer, Black patients who received surgery (which is part of the treatment paradigm for localized lung cancer) at academic facilities experienced better survival than Black and White patients who received surgery at community facilities. 21 Further research is needed to disentangle the mechanisms that produce racial disparities and inform prevention strategies at the health care organization level.…”
Section: Introductionmentioning
confidence: 99%